Treatment of Textile Dyes by Bio-chemical Process in Stirred Tank Sequencing Batch Bioreactor - Khan, Maksudur R.; Saha, Pradip; Dep, T. K.; Sony, S. Y.; Baishnab, Ajit Chandra (Bangladesh Journals OnLine (BanglaJOL), 2012)
A bacterial isolate Pseudomonas sp. was isolated from the solid waste slump collected from a local duping site of Sylhet district and was efficiently utilized for the removal of dye (Orange 3R) from simulated synthetic waste water in a lab scale Stirred Tank Sequencing Batch Bioreactor (STSBBR) in batch mode. A reactor with 2 L capacity (working volume 0.5 L) equipped with suitable control means and stirring mechanism was operated at room temperature and pH 6.6 ± 1 in fill-react-settling-draw mode with different initial dye concentrations (50, 100, 150, 200 & 300 ppm) where the hydraulic retention time was maintained for 12-72 hours depending on the adaptation of waste water by the bacterial strain. The efficiency of the reactor was analyzed with respect to three strands and found to be negative correlation with the concentration of the dye. Overall color, COD, and BOD in the Stirred tank bioreactor system (STSBBR) were removed by 49.67, 37.45 and 33.89%, respectively with 50 ppm dye concentration and HRT of 24 h. The efficiency of the reactor was found to be in negative correlation with the concentration of the dye. This STSBBR system was found very effective for efficient biological treatment of such dyeing industry waste water by the bacterial strain Pseudomonas sp.